Control of Methylene Blue Photo-Oxidation Rate over Polycrystalline Anatase TiO2 Thin Films via Carrier Concentration - Ong, S. W. Daniel (2016)
Reaction rates on photocatalytic surfaces would often benefit greatly if minority photocar-riers could be driven more efficiently to the surface through the manipulation of electric fields within the semiconductor. Such field-induced manipulation of photocurrent is commonplace in conventional optoe-lectronics, but translation to photochemistry and photoelectrochemistry has lagged. The present work demonstrates quantitatively that manipulation of the spatial extent of band bending via background carrier concentration can increase photoreaction rates by a factor of five or more in the case of methylene blue photodegradation over thin-film polycrystalline anatase TiO2. A quantitative photocurrent model fits closely to experimental rate data with no adjustable parameters.